Konsep Dasar Sejarah Membentuk Karakter Serta Integrasinya Pada Pelajaran IPS di Sekolah Dasar - Nuriafuri, Rafika (Pena Edukasia, 2024)
History serves as a crucial pillar in comprehending the long journey of human civilization. The fundamental concept of history encompasses various aspects, ranging from understanding the origins of humanity and the development of civilizations to comprehending significant events and their impacts on the contemporary world. The research methodology employed is qualitative descriptive with a literature review approach. Through literature analysis, the author explores basic historical concepts, including understanding chronology, causes and effects, and historical contexts, as well as how the integration of these concepts in social studies education can yield positive impacts. The findings of this research indicate that the integration of basic historical concepts in elementary social studies education has significant implications in shaping students' characters, such as fostering a strong national identity, appreciation for cultural values, the development of critical and analytical attitudes, and instilling good moral values. These implications contribute significantly to strengthening the Indonesian national identity through primary education.